Uncovering the role of Rad51 in homologous recombination-mediated antigenic diversification in the human malaria parasite Plasmodium falciparum - Vydyam, Pratap; Roy, Nabamita; Bhattacharyya, Mrinal Kanti (Frontiers in Molecular Biosciences, 2023)
The human malaria parasite Plasmodium falciparum maintains the chronicity of infections through antigenic variation, a well-coordinated immune evasion mechanism. The most prominent molecular determinant of antigenic variation in this parasite includes the members of the var multigene family. Homologous recombination (HR)-mediated genomic rearrangements have been implicated to play a major role in var gene diversification. However, the key molecular factors involved in the generation of diversity at var loci are less known. Here, we tested the hypothesis that PfRad51 could carry out recombination between var genes that are not homologous but homeologous in nature. We employed the whole-genome sequencing (WGS) approach to investigate recombination events among var sequences over 100 generations and compared the rate of sequence rearrangement at the var loci in both PfRad51-proficient and -deficient parasite lines. This brief report provides evidence that the loss of the key recombinase function renders the parasite with inefficient HR and results in fewer recombination events among the var sequences, thereby impacting the diversification of the var gene repertoire.